2006
DOI: 10.1111/j.1600-6143.2006.01429.x
|View full text |Cite
|
Sign up to set email alerts
|

Successful In Vitro Priming of EBV-Specific CD8+ T Cells Endowed with Strong Cytotoxic Function from T Cells of EBV-Seronegative Children

Abstract: Epstein-Barr virus (EBV)-seronegative transplant recipients are at high risk of developing EBV-associated post-transplant lymphoproliferative disorder (PTLD), and would maximally benefit from an EBV-directed T-cell therapy for prevention or treatment of PTLD. So far, efforts to activate CD8+ EBV-specific cytotoxic T lymphocytes (CTL) endowed with high specific cytotoxicity from EBV-seronegative children have failed. We compared the CD8+ CTL priming efficiency of three different modified activation protocols, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…Using a similar priming method with neonatal moDC and CMV antigen, others have found that there is a predominance of CD45R Ϫ CD27 ϩ T cells in the CMV-positive cell population (45). Similar to our results, Comoli et al (9) found a predominant population of CD45RA Ϫ CD27 Ϫ , and a secondary population of CD45RA ϩ CD27 Ϫ , CD8 ϩ T cells specific for EBV peptide in primed cultures from children. Likewise, Salio and colleagues (52) have reported that cord blood CD8 ϩ T cells primed to melanoma peptide are predominately CD45 Ϫ CCR7 Ϫ CD27 ϩ .…”
Section: Fig 4 Priming Of Cd8supporting
confidence: 91%
See 1 more Smart Citation
“…Using a similar priming method with neonatal moDC and CMV antigen, others have found that there is a predominance of CD45R Ϫ CD27 ϩ T cells in the CMV-positive cell population (45). Similar to our results, Comoli et al (9) found a predominant population of CD45RA Ϫ CD27 Ϫ , and a secondary population of CD45RA ϩ CD27 Ϫ , CD8 ϩ T cells specific for EBV peptide in primed cultures from children. Likewise, Salio and colleagues (52) have reported that cord blood CD8 ϩ T cells primed to melanoma peptide are predominately CD45 Ϫ CCR7 Ϫ CD27 ϩ .…”
Section: Fig 4 Priming Of Cd8supporting
confidence: 91%
“…Likewise, Salio and colleagues (52) have reported that cord blood CD8 ϩ T cells primed to melanoma peptide are predominately CD45 Ϫ CCR7 Ϫ CD27 ϩ . However, different modes of in vitro priming of T cells can result in various degrees of memory T-cell differentiation (9). Clearly, one should be cautious about interpreting T-cell phe-…”
Section: Fig 4 Priming Of Cd8mentioning
confidence: 99%
“…Moreover, the requirement that donors be seropositive donors to produce/expand specific T cells has been at least partly solved by the use of in vitro stimulation approaches for antigen-specific stimulation of naive (even CB-derived) T lymphocytes [65,66].…”
Section: Culture Protocolsmentioning
confidence: 99%
“…Additional cytokines released by activated T-helper cells facilitate PMN differentiation from HSC precursors (7). and cytokine cocktails including IL7, IL12 and IL15 for T-cell expansion [57][58][59]60 ]. Since this approach is demanding and time consuming, the use of T-cell lines stored in a biobank is a viable alternative.…”
Section: Special Requirements For the Production Of Therapeutic T-celmentioning
confidence: 99%